MANAJEMEN PENGELOLAAN KELAS DALAM MENINGKATKAN MUTU PEMBELAJARAN PAI DI SMP ISLAM DARUL ULUM CONDONG GADING TAHUN PELAJARAN 2017-2018 - Tri Wisudaningsih, Endah; M. Huzin (LP3M UNZAH GENGGONG, 2019)
Abstract Teaching and learning processes held in several schools as a center for formal education are more intended to direct changes in themselves in a planned manner both in terms of cognitive, affective and psychomotor. The role of the teacher is very important in education. Good or bad education is influenced by how a teacher can manifest and apply his contribution to formal institutions to realize the intelligence of the nation and the ideals of the country, so that between teacher and education is an inseparable component. Therefore, In reality, in the field of Islamic Religious Education subjects today the quality is still vulnerable because it has not reached the desired target adequately, especially in public schools. In addition to this reality, there is an assumption that